Implementation of nursing case management to improve community access to care: A scoping review - Alenda Dwiadila Matra Putra; Ayyu Sandhi (Belitung Raya Foundation, Indonesia, 2021)
Background: Case management is an approach used to help patients locate and manage health resources as well as to enhance effective communication among patients, families, and health systems. Nurses’ role as case managers has been proven effective in reducing healthcare costs among patients with chronic diseases. However, little is known about its implementation in improving access to care in community-based settings. Objectives: This scoping review aimed to examine the components of nursing case management in improving access to care within community settings and to identify the issues of community-based nursing case management for future implications. Design: This study was conducted following the framework of scoping review.Data Sources: The authors systematically searched five electronic databases (CINAHL, PubMed, Science Direct, Scopus, and Google Scholar) for relevant studies published from January 2010 to February 2021. Only original studies involving nurses as one of the professions performing case management roles in the community-based settings, providing 'access to care' as the findings, were included. Review Methods: The article screening was guided by a PRISMA flowchart. Extraction was performed on Google Sheet, and synthesis was conducted from the extraction result.Results: A total of 19 studies were included. Five components of nursing case management to improve access to care were identified: 1) Bridging health systems into the community, 2) Providing the process of care, 3) Delivering individually-tailored health promotion and prevention, 4) Providing assistance in decision making, and 5) Providing holistic support. In addition, three issues of nursing case management were also identified: 1) Regulation ambiguity, 2) High caseloads, and 3) Lack of continuing case management training.Conclusion: Care coordination and care planning were the most frequent components of nursing case management associated with access to care. These findings are substantial to improve nurses' ability in performing the nursing process as well as to intensify nurses’ advocacy competence for future implications.